Advances in plant-based raw materials for food 3D printing - Zhihao Liu; Xinna Hu; Shuyu Lu; Bo Xu; Chenyu Bai; Tao Ma; Yi Song (Journal of Future Foods)
Three-dimensional (3D) printing is an emerging technology in the food industry, and in recent years, with its unique advantages, it has been widely used in the food industry. Its organic combination with food production provides customization, personalization, and intelligent features. The combination of plant-based food raw materials with 3D printing technology to produce food has a broad space for development in catering to people's pursuit of healthy diets. To facilitate a more comprehensive understanding of the application of plant-based food raw materials in food 3D printing, we classified inks into molten, soft, and hydrogel materials according to their state of existence and rheological properties under different conditions. The applications of different plant-based raw food materials in 3D printing are reviewed separately by ink type. This is expected to enrich the coverage of the review in related fields, enabling a quick understanding of the research direction and enriching the research content.